LncRNA OIP5-AS1 Promotes the Proliferation of Hemangioma Vascular Endothelial Cells via Regulating miR-195-5p/NOB1 Axis - Zhang, Jiayu; Zhao, Tiancheng; Tian, Leilei; Li, Yezhou (Frontiers in Pharmacology, 2019)
Background: Hemangioma, which is a benign vascular neoplasm, has been demonstrated to be the most common tumor of infancy, resulting from aberrant proliferation of endothelial cells and pericytes. Objective: The aim of this study was to determine the role of lncRNA OIP5-AS1 on the proliferation and metastasis of human hemangioma endothelial cells (HemECs). Methods: In this study, we examined the expression of OIP5-AS1 and miR-195-5p in hemangiomas patients. The effects of knockdown or ectopic expression of OIP5-AS1 on the viability, proliferation and apoptosis of HemECs were explored. Rescue assays were performed to explore the effects of OIP5-AS1/miR-195-5p/NOB1 axis on biological behaviors in the HemECs. Results: It was found that OIP5-AS1 was overexpressed in both hemangioma tissues and HemECs cells. OIP5-AS1 knockdown suppressed the proliferation, migration, and invasion of HemECs cell, while overexpression of OIP5-AS1 had opposite effects LncRNA OIP5-AS1 acted as a ceRNA through binding with miR-195-5p to upregulate NOB1 in HemECs. Conclusion: Taken together, lncRNA OIP5-AS1 acted as a ceRNA to drive proliferation, migration and invasion of HemECs through regulating miR-195-5p/NOB1 axis.